Postharvest quality of two orange‐fleshed sweet potato [Ipomoea batatas (L) Lam] cultivars as influenced by organic soil amendment treatments - Atuna, R.A.; Aduguba, W.O.; Alhassan, A.; Abukari, I.A.; Muzhingi, T.; Amagloh, F.K.; Mbogo, D. (Wiley, 2018)
Two orange‐fleshed sweet potato cultivars: Apomuden and “Nane” were grown on cow dung‐, chicken manure‐, compost‐amended soils, and untreated soil. Apomuden is a variety, while “Nane” is being evaluated to be released in Ghana. The storage roots (SRs) were harvested at 3 months, cured by heaping the SRs and covering with the sweet potato foliage for 7 days in the field. The cured SRs were kept in an evaporative cool chamber to study the effect of soil amendment treatments on weight loss, rot, some nutrient composition, and sensory attributes. Boiled SRs were assessed by 70 untrained panelists after 7 weeks of storage based on the following: general appearance, sweetness, finger‐feel firmness, and overall acceptability using a 5‐point hedonic scale (1 = dislike extremely to 5 = like extremely). Percent rot for “Nane” showed a linear trend, while that of Apomuden was nonlinear. Both cultivars showed similar trends in terms of cumulative weight loss with “Nane” recording lower weight loss compared with Apomuden. A significant (p < 0.001; r = 0.71) strong positive correlation was observed between weight loss and rots. “Nane” had higher dry matter (37.15% vs. 30.19%; p < 0.001, respectively) and starch content (59.16% vs. 51.86%; p < 0.001, respectively) than Apomuden. Stored SRs grown on chicken manure‐amended soil recorded the highest protein (6.41%; p < 0.001) and β‐carotene (16.64 mg/100 g; p < 0.001) content than the other treatments. There was a 35% decline in β‐carotene for Apomuden, while “Nane” increased by 24% at the end of the 7‐week storage. “Nane,” the cultivar with high dry matter content had good storage properties than Apomuden. Stored SRs cultivated on soils amended with chicken manure had higher β‐carotene and protein content. All sensory attributes ranged from 3.35 to 3.68 indicating a good consumer preference for both cultivars irrespective of the soil amendment treatment applied.